"Bowel prep hyponatremia" – a state of acute water intoxication facilitated by low dietary solute intake: case report and literature review. Issue 1 (December 2017) - Windpessl, Martin; Schwarz, Christoph; Wallner, Manfred
Abstract Background Symptomatic hyponatremia is considered a rare complication of oral bowel preparation for colonoscopy. The pathophysiology underlying this phenomenon has been widely regarded as a mere sequela of excessive arginine vasopressin (AVP) release. Case presentation This case describes a 61-year old woman who developed acute hyponatremic encephalopathy when preparing for elective outpatient lower endoscopy. She had had negligible oral solute intake for two days and ingested four liters of clear fluid within two hours. On admission, the patient was agitated and had slurred speech. Treatment with hypertonic saline lead to full recovery. A brisk aquaresis confirmed acute dilutional hyponatremia. Conclusion Apart from elevated AVP-levels, the amount and speed of fluid intake and concomitant low-solute intake constitute important risk factors in the development of clinically relevant hyponatremias in patients undergoing colonoscopies. Understanding that the cause of sodium imbalance in this scenario is multifactorial and complex is pivotal to recognizing and ideally preventing this complication, for which we propose the term "bowel prep hyponatremia".